(untitled) (Journal of history-rus, 2023)
Annotation. The article discusses the reasons and reveals the specifics of why the German troops in the first half of the XX century were called “Huns”. In particular, starting with the history of the emergence of this trend of equating Germans with Huns, the author conducts an extensive analysis of its manifestations during the First and Second World Wars. In addition, the author in his research work analyzes the positions and views of Europeans in relation to the Huns, exploring the application of the name “Huns” to the Germans as part of anti-German propaganda work in the early XX century. The role of the agitation of Anglo-American and other Western states in shaping the image of the Germans as “wild Huns” is reflected. In addition, special attention is paid to the fact that within the framework of which approach positions are formed. In the article, the author also offers his own assumptions about why the idea in which Germans are called Huns, widely used in the early XX century, lost its viability and began to cease its use during World War II. In the final part, the author of the study, based on the results obtained, draws conclusions about the image of the Huns in the minds of the European population. Keywords: Huns, German army, Germans, Attila, World War I, World War II, barbarian